Pendidikan Melalui Lensa Fundamentalisme, Modernisme, dan Liberalisme - Pohan, Heni Mulyani; Sahara, Nur; Widodo, Joko; Tobroni, Tobroni (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
This research aims to explore educational paradigms through various ideological lenses, namely fundamentalist, modernist and liberal, in the context of finding the influence between education and the three ideologies of fundamentalist, liberalism and modernism. In achieving this goal, this research adopts a qualitative approach to understand how each ideological view contributes to the development of holistic and inclusive education. By focusing on the discourse between maintaining traditional values in education and encouraging innovation to adapt to current and future needs, this research offers a comprehensive perspective on how educational institutions can embrace these aspects to create a dynamic and relevant learning ecosystem. It is hoped that the research results will provide insight for policy makers, educational practitioners and other stakeholders in formulating educational strategies that combine harmonization between respect for cultural heritage and the application of innovative approaches that encourage students' creativity and critical skills.